Analysis of two microphone method for feedback cancellation - Nakagawa, C.; Nordholm, S.; Yan, Wei-Yong (Institute of Electrical and Electronics Engineers Inc., 2015)
Acoustic feedback cancellation in hearing aids makes use of adaptive filters to continuously identify and track variations to the feedback path. One of the biggest problems remaining in using adaptive filters for feedback cancellation is the biased estimation of the filter's coefficients. In order to remove the undesired correlation between the loudspeaker and incoming signal, a recent alternative scheme proposed to employ an additional microphone. This microphone can provide added information to obtain an incoming signal estimate. This estimate is removed from the primary microphone signal to create the error signal which adapts the canceler's coefficients. This letter provides the theoretical analysis for the two microphone method. It presents analytic expressions showing that the optimal solution is no longer dependent on the signal correlation aforementioned but is now mainly determined by the additional feedback path. Finally, it demonstrates simulation results with the prediction error method in terms of misalignment and maximum gain for a proposed microphone placement. The results show that a more stable solution is obtained with the proposed two microphone approach. © 2014 IEEE.